The Holy Communion and African rituals: An encounter between African religion and Christianity - Ngcobo, Themba E. (HTS teologiese studies, 2020)
African lifestyle is informed, influenced and guided by African cosmology or cosmologies. These cosmologies (especially from the AmaZulu tribes, who are the focus of this study) shape social norms that are drawn from and explained by various indigenous knowledge systems that view the cosmology as intertwined. Consequently, according to this view, the spiritual world is not necessarily divorced from the physical world. This configuration of rationality could be observed during traditional and cultural gatherings in which myth is not only orally narrated but re-lived through rituals. In such cases, rituals provide a sphere where both the human world and the spiritual world converge in sharing a mythic experience represented in meals, drinks, songs, clapping of hands and dances. This convergence of God, amadlozi or badimo (generally translated as ‘ancestors’ or ‘predecessors’) brings the lived experience of the previous generation to reality. Therefore, the main argument in this contribution would be that the story of Jesus could still be re-lived through its most significant rituals such as the Holy Communion. This article reflects on the ritual of Holy Communion, which more emphatically addresses African cosmological views. The question of exclusivism of participation in this ritual is addressed to probe their individualistic pattern, which is perhaps more Western than African.